Development and evaluation of the Jönköping Dental Fear Coping Model: a health professional perspective. (4th July 2018) - Brahm, Carl-Otto; Lundgren, Jesper; Carlsson, Sven G.; Nilsson, Peter; Hägglin, Catharina
Abstract: Objective: The purpose of this study was to design a structured treatment model focusing on all levels of adult's dental fear, the Jönköping Dental Fear Coping Model (DFCM). The aim was to study the DFCM from a dental health professional perspective. Material and methods: The DFCM was studied by means of quantitative and qualitative analyses. Nine dental clinics participated in Period I (pre-intervention/standard care), and 133 dental health professionals (dentists, dental hygienists, dental assistants) and 3088 patients were included. After completion of Period I, four of the clinics were randomized to Period II (intervention), beginning with the professionals undergoing DFCM training. Following that, 51 dental health professionals treated 1417 patients according to the DFCM. The other five clinics served as controls. Results: Half or more of the dental health professionals assessed the model as better than standard care, regarding anamnesis and diagnostics, communication and contact, and understanding of patients and dental fear. The dental health professionals reported higher tension in their fearful patients in Period II compared with Period I, possibly due to their increased awareness of dental fear. Conclusions: The qualitative data suggest that dental health professionals find the DFCM beneficial in routine dental care. The model promotes a holistic approach to the treatment of adult patients. However, stress among the professionals was not reduced when measured, neither quantitatively nor qualitatively. It is important to evaluate the model in further studies to make it possible to draw generalizable conclusions.